Pelatihan Pembuatan Media Pembelajaran Menggunakan Canva bagi Guru SMPN 1 Tegalampel Bondowoso - Vega Kartika Sari; Riza Yuli Rusdiana; Widya Kristiyanti Putri (Universitas Mataram, 2021)
The use of learning media by utilizing technology is very important needed during a pandemic. Learning media can be in the form of visual, audio, and audio visual. Attractive learning media can create memorable and easier-to-understand learning activities. Canva is a graphic design application that helps users to create various types of creative materials online. Using Canva as a learning medium can make it easier for teachers to design learning media. Almost all teachers at SMPN 1 Tegalampel have not been able to make video-based learning media so that the delivery of material to students is still low. This activity aims to provide training in making learning media using Canva for teachers at SMPN 1 Tegalampel, Bondowoso. The training activities were carried out in several stages, namely socialization, practice, and evaluation. The results of the activity showed that the training participants got an increase in knowledge and skills related to learning media using the Canva application.